PENERAPAN METODE LEARNING COMMUNITY TERHADAP PENINGKATAN KEMAMPUAN SHOOTING PADA TIM SEPAKBOLA PUTRI KABUPATEN MAJALENGKA - Indrayogi Indrayogi; Bayu Dwi Febrianto (Universitas Majalengka, 2021)
ABSTRACT. Based on empirical data, it was found that most of the female soccer players in Majalengka Regency were less able to perform basic shooting techniques well, this was because they had not been given proper training methods and were less varied and effective in reaching all athletes equally, so that the athletes' motivation to improve their abilities was do shooting. The researcher raised a problem about the application of community learning methods to increase the ability of Majalengka female soccer players which aims to apply community learning methods to increase the shooting ability of soccer players in Majalengka district. The samples taken were all athletes of the women's soccer team in Majalengka district, allegedly 24 players. While the method used in this research is a quantitative method with an experimental approach. The instruments used were practical tests and observation sheets. From the analysis of research data which states that this method has an impact on increasing the ability of basic football techniques, especially shooting, because in practice athletes are required to be in the training process. The conclusion is that the application of community learning methods has an effect on increasing the shooting ability of female soccer players in Majalengka district. Keywords: Learning Community; Shooting; Women Football ABSTRAK. Berdasarkan data empiris, menemukan bahwa sebagian besar pemain sepakbola putri Kabupaten Majalengka kurang mampu melakukan teknik dasar shooting dengan baik, hal tersebut dikarenakan belum diberikannya metode latihan yang tepat dan kurang variatif serta efektif menjangkau seluruh atlet secara merata, sehingga kurangnya motivasi atlet dalam meningkatkan kemampuannya dalam melakukan shooting. Peneliti mengangkat masalah tentang pengaruh penerapan metode learning community terhadap peningkatan kemampuan shooting pemain sepakbola putri Majalengka yang bertujuan untuk mengetahui penerapan metode learning community terhadap peningkatan kemampuan shooting pemain sepakbola putri kabupaten Majalengka. Sampel yang diambil adalah atlet seluruh pemain tim sepakbola putri kabupaten Majalengka yang berjumlah 24 pemain. Sedangkan metode yang digunakan pada penelitian ini adalah metode kuantitatif dengan pendekatan eksperimen. Instrumen yang digunakan adalah test praktek dan lembar observasi. Dari hasil analisis data penelitian menyatakan bahwa metode ini memberikan dampak peningkatan kemampuan teknik dasar sepakbola khususnya shooting, karena pada pelaksanaanya atlet dituntut untuk bekerjasama dalam proses latihan. Kesimpulannya yaitu penerapan metode learning community berpengaruh terhadap peningkatan kemampuan shooting pemain tim sepakbola putri kabupaten Majalengka. Kata Kunci: Learning Community; Shooting; Sepakbola Putri